Cellulose-Amine Porous Materials: The Effect of Activation Method on Structure, Textural Properties, CO2 Capture, and Recyclability - Krupšová, Sarah; Almáši, Miroslav (Molecules (Basel, Switzerland), 2024)
CO2 capture via physical adsorption on activated porous carbons represents a promising solution towards effective carbon emission mitigation. Additionally, production costs can be further decreased by utilising biomass as the main precursor and applying energy-efficient activation. In this work, we developed novel cellulose-based activated carbons modified with amines (diethylenetriamine (DETA), 1,2-bis(3-aminopropylamino)ethane (BAPE), and melamine (MELA)) with different numbers of nitrogen atoms as in situ N-doping precursors. We investigated the effect of hydrothermal and thermal activation on the development of their physicochemical properties, which significantly influence the resulting CO2 adsorption capacity. This process entailed an initial hydrothermal activation of biomass precursor and amines at 240 °C, resulting in C+DETA, C+BAPE and C+MELA materials. Thermal samples (C+DETA (P), C+BAPE (P), and C+MELA (P)) were synthesised from hydrothermal materials by subsequent KOH chemical activation and pyrolysis in an inert argon atmosphere. Their chemical and structural properties were characterised using elemental analysis (CHN), infrared spectroscopy (IR), scanning electron microscopy (SEM), and thermogravimetric analysis (TG). The calculated specific surface areas (SBET) for thermal products showed higher values (998 m2 g-1 for C+DETA (P), 1076 m2 g-1 for C+BAPE (P), and 1348 m2 g-1 for C+MELA (P)) compared to the hydrothermal products (769 m2 g-1 for C+DETA, 833 m2 g-1 for C+BAPE, and 1079 m2 g-1 for C+MELA). Carbon dioxide adsorption as measured by volumetric and gravimetric methods at 0 and 25 °C, respectively, showed the opposite trend, which can be attributed to the reduced content of primary adsorption sites in the form of amine groups in thermal products. N2 and CO2 adsorption measurements were carried out on hydrothermal (C) and pyrolysed cellulose (C (P)), which showed a several-fold reduction in adsorption properties compared to amine-modified materials. The recyclability of C+MELA, which showed the highest CO2 adsorption capacity (7.34 mmol g-1), was studied using argon purging and thermal regeneration over five adsorption/desorption cycles.
Keywords: pyrolysis; amines; cellulose; carbon dioxide storage; hydrothermal synthesis